2018
DOI: 10.22237/jmasm/1529418622
|View full text |Cite
|
Sign up to set email alerts
|

An explanatory study on the non-parametric multivariate T2 control chart

Abstract: Most control charts require the assumption of normal distribution for observations. When distribution is not normal, one can use non-parametric control charts such as sign control chart. A deficiency of such control charts could be the loss of information due to replacing an observation with its sign or rank. Furthermore, because the chart statistics of T 2 are correlated, the T 2 chart is not a desire performance. Non-parametric bootstrap algorithm could help to calculate control chart parameters using the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Both types of control chart produced out-of-control signals from different points, hence inconclusive results obtained. This study proposes the application of non-parametric multivariate T 2 control chart as an alternative tool for process monitoring whenever the multivariate normality assumption is violated (Mostajeran & Iranpanah, 2018;Boone & Chakraborti, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Both types of control chart produced out-of-control signals from different points, hence inconclusive results obtained. This study proposes the application of non-parametric multivariate T 2 control chart as an alternative tool for process monitoring whenever the multivariate normality assumption is violated (Mostajeran & Iranpanah, 2018;Boone & Chakraborti, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the principal component scores produced by a standard PCA for only numerical variables, the scores produced by PCA Mix do not follow multivariate normal distribution or any known family of distribution (Ashan et al 2018). To solve this problem, we use a nonparametric methodbootstrap resampling (Mostajeran et al 2018;Phaladiganon et al 2011)to estimate the control limit for the 2 chart based on PCA Mix. Bootstrap resampling, first introduced by Efron (1979), is one of the most widely-used methods to estimate the parameters of an unknown distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In Mostajeran et al [7], the authors presented the use of non-parametric bootstrap multivariate control charts |S|, W, and G, and this method is grounded upon the use of bootstrapped data in the estimation of the in-control state. In this study, the authors succeeded in obtaining satisfactory performance of bootstrap [12] demonstrated the application of a bootstrap multivariate control chart and compared it with a Hotelling's T 2 parametric multivariate control chart, a multivariate sign control chart, and a multivariate Wilcoxon control chart. A simulation study was employed for the purpose.…”
Section: Introductionmentioning
confidence: 99%